Peningkatan Daya Saing Wilayah Berbasis Potensi Ekonomi Lokal - Faradillah Herlin (Universitas Muhammadiyah Jambi, 2014)
Region development policy must be oriented to increase competitiveness base on local economic potential. The policy purposed is support sustainable development process. So need to identification effort for potential commodity base on local economic potential and agribusiness development policy is integrated to get this purpose, must be used industry cluster approach.